Perioperative acute kidney injury in surgical treatment of renal cancer: pathogenesis, therapy of early and late complications - S. V. Popov; R. G. Guseynov; Ye. V. Pomeshkin; K. V. Sivak; V. V. Perepelitsa; K. A. Nadein; N. S. Bunenkov; A. S. Ulitina (Исследования и практика в медицине, 2023)
The development of acute renal injury is due to a number of factors both on the part of the patient (age, concomitant pathology, objective status) and the oncological process (stage of the disease, localization, volume of surgical intervention, access, etc.). Acute renal injury in patients with kidney cancer after surgical treatment may be accompanied by the development of early (hyperhydration, electrolyte balance disorders, hyperkalemia, acid‑base condition disorders, uremic intoxication) and late chronic kidney disease complications. The incidence of these complications increases with an increase in the volume of kidney resection, as a result of which it is important to take into account risk factors, timely diagnosis of the degree of kidney damage and medical measures aimed at restoring kidney function. Currently, the possibility of using various molecules as early markers of kidney damage, which help not only assess the presence of kidney damage, but also localize it, is being studied. For example, albumin, serum cystatin C, alpha 1‑microglobulin, P2‑microglobulin – markers of glomerular damage, NGAL, KIM‑1; L‑FABP, urine cystatin‑C, IL‑18 – reflect damage to the proximal tubule, GST, NGAL – distal tubule, calibindin D28 ‑ characterizes damage to the collecting duct, osteopontin, NHE‑3 – are associated with damage to the loop of Henle. Measures of a curative and preventive nature (infusion therapy, anti‑ischemic protection, modulation of ferroptosis, renal replacement therapy), as well as dynamic monitoring of the main biomarkers of renal damage are aimed at preventing the persistence of the pathological process with a possible outcome into chronic kidney disease, which is especially undesirable in patients with single kidney cancer. The main directions of medical and preventive measures in patients with acute kidney injury should be considered: 1) the fastest possible elimination or minimization of the effect of tumor tissue; 2) control and correction of life‑threatening complications of renal dysfunction (hyperhydration, electrolyte balance disorders (hyperkalemia), acid‑base state, uremic intoxication). Methods of anti‑ischemic protection include a number of surgical techniques aimed at 1) minimizing ischemia time, 2) reducing the intensity of volatile metabolic processes in the kidney, 3) training renal parenchyma for hypoxic conditions (receiving ischemic preconditioning).Duration of renal ischemia represents an important modifiable factor affecting early and distant renal function in surgically exposed patients. The article analyzes modern scientific data on the problem of postoperative acute kidney injury in renal cancer surgery.